Lesevarianten zu Günter Grass’ Lektüren in Polen - Szumowska, Henryka (Studia Germanica Posnaniensia, 2018)
According to what is told in the title of this article it deals with many variants of reading and understanding Günter Grass's works which have prevailed the reading of this writer's, artist's and publicist's works in Poland since the appearance of his first books as early as 1958 until the present day. Let us add, therefore, that reading of Grass's works in Poland has had its long-lasting career - the origin and invariably "intensive" course, independently of the fact that the prolific literary output of Günter Grass has been represented on Polish book market by only two prose works, namely “The cat and the mouse” and “The brass drum”, selected poetic works and fragments of some of his other novels, like for instance “The Flounder”. Nevertheless, this writer is a well-known and recognized individuality and personality not only because of his being born in Gdańsk, his numerous friends and relatives in Poland, but also because of his particular interest in Poland, his many visits to our country and celebrations connected with them, organized especially magnificently at the sea-shore, mostly in Gdańsk, and also in Warsaw, Wrocław and, more recently in Poznań.